An in-depth analysis of the representation of speech acts and language functions in Libyan public high school English textbooks - Alhadi Ali Ahmed, Fatma; Mohammadzadeh, Behbood; Mazlum, Farhad (Frontiers in Psychology, 2023)
Abstract The research attempts to inspect the frequency of speech acts and language functions in the 21st Century English for Libya Secondary 1,2 and 3 coursebooks and workbooks. Two frameworks were employed to analyze the speech acts and language functions present in this series of textbooks. Five-course books and five workbooks in the same series were examined for the former pragmatic features. The results specified that all the textbooks had shortages in the declarative speech act and the imaginative language function and showed signs of unequal distribution of these pragmatic features throughout all the series of the textbooks. The findings highlight that the unequal frequency and distribution of these pragmatic variables are in line with previous studies and, therefore, provide implications for EFL curriculum designers and language practitioners.